Impact of a one-year school-based teacher-implemented nutrition and physical activity intervention: main findings and future recommendations - Carla Habib-Mourad; Lilian A. Ghandour; Carla Maliha; Nancy Awada; Michèle Dagher; Nahla Hwalla (BMC Public Health, 2020)
Abstract Background The aim of the current study is to describe the effectiveness of a school-based intervention when delivered by a non-nutrition specialist (trained schoolteachers) as compared to an expert in nutrition. Methods Two trials of the same school-based intervention using the same intervention package were delivered, one by nutritionists and another by trained schoolteachers. The intervention focused mainly on dietary behaviours, as well as physical activity. In both trials, purposively selected schools were randomized to intervention or control groups; students (aged 9–11 years) in both groups were compared at post-test on knowledge and self-efficacy scores, as well as dietary and physical activity behaviours, controlling for their baseline status on the various measures. All analyses accounted for clustering at the school level. Results In both trials, a statistically significantly greater improvement was observed for both the knowledge and self-efficacy scores in intervention vs. school students. When the programme was delivered by trained schoolteachers, frequency of breakfast intake was increased, crisps consumption was reduced, but no change in fruit and vegetable consumption was observed (latter increased when delivered by nutrition professionals only). Physical activity did not improve in both trials. Conclusion Trained schoolteachers can have a positive impact on students’ dietary behaviours with the appropriate training to ensure they are equipped with the right information, skills, and resources to deliver the programme with the highest fidelity. Trial registration ClinicalTrial.gov Identifier: NCT03040271. Retrospectively registered on 2 February 2017.